2021
DOI: 10.3389/fphar.2020.617085
|View full text |Cite
|
Sign up to set email alerts
|

Contributive Role of TNF-α to L-DOPA-Induced Dyskinesia in a Unilateral 6-OHDA Lesion Model of Parkinson’s Disease

Abstract: Our present objective was to better characterize the mechanisms that regulate striatal neuroinflammation in mice developing L-DOPA-induced dyskinesia (LID). For that, we used 6-hydroxydopamine (6-OHDA)-lesioned mice rendered dyskinetic by repeated intraperitoneal injections of 3,4-dihydroxyphenyl-L-alanine (L-DOPA) and quantified ensuing neuroinflammatory changes in the dopamine-denervated dorsal striatum. LID development was associated with a prominent astrocytic response, and a more moderate microglial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Differences in survival time after MPTP and methodological approaches could account for the different results obtained in the MPTP + L-Dopa monkeys between these studies. Several preclinical studies in rodent models of PD have shown that treatment with L-Dopa induces or exacerbates inflammation via a direct involvement of microglia releasing pro-inflammatory cytokines promoting an initiation and/or development of dyskinesias [ 72 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. In fact, the strong positive correlations between Iba1 levels and dyskinetic scores measured in several basal ganglion nuclei in the present study strongly support a direct link between LID and microglial reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in survival time after MPTP and methodological approaches could account for the different results obtained in the MPTP + L-Dopa monkeys between these studies. Several preclinical studies in rodent models of PD have shown that treatment with L-Dopa induces or exacerbates inflammation via a direct involvement of microglia releasing pro-inflammatory cytokines promoting an initiation and/or development of dyskinesias [ 72 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. In fact, the strong positive correlations between Iba1 levels and dyskinetic scores measured in several basal ganglion nuclei in the present study strongly support a direct link between LID and microglial reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, microglial cell isolation occurs spontaneously after 14-18 days of culture. When required, purified microglial cells were maintained for up to 1 more week in culture flasks by adding 2-3 mL of DMEM supplemented with penicillin/streptomycin and only 1% of FCS [28]. Subcultures were produced by trypsinizing purified microglial cell cultures with 0.05% trypsin-EDTA for 5 min.…”
Section: Isolation Of Microglial Cells and Production Of Microglial Subculturesmentioning
confidence: 99%
“…As ERK 1/2 phosphorylation was a crucial upstream event prior to the IEG transcription, we speculated that JQ1-blocked ERK 1/2 phosphorylation might be attributed to its suppression of the NF-κB-mediated gene expression of TNF-α and IL-1 β. With intermittent L-dopa stimulation, an increased cortico-striatal synaptic glutamate elicited an elevation of glia-derived TNF-α, which further enhanced the release of glutamate from the cortical neurons in a self-reinforcing manner ( Dos Santos Pereira et al, 2021 ). The hyperactivity of cortico-striatal glutamatergic transmission positively contributed to the occurrence of LID by inducing neuron-expressed receptor-mediated ERK1/2 phosphorylation ( Picconi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have reported that BET proteins were involved in the canonical NF-κB activation pathway in autoinflammation disorders, injury, infection, and chronic morbid conditions, and inhibition of the BET protein function effectively suppresses the NF-κB-mediated pro-inflammatory expression, alleviating the neuroinflammation response in these pathological conditions ( Jahagirdar et al, 2017 ; Wang et al, 2018 ; Sánchez-Ventura et al, 2019 ; Zhou et al, 2019 ). In the DA-denervated striatum of LID animal models, the inflammatory status is characterized by the overexpression of pro-inflammatory substances of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and inducible nitric oxide synthase (iNOS), which has been reported to be involved in the mechanisms of LID ( Barnum et al, 2008 ; Bortolanza et al, 2015 ; Dos Santos Pereira et al, 2021 ). A recent study reported that a BET inhibitor JQ1 efficiently alleviated LID; however, its association with the impact of inhibition of the BET protein function on the NF-κB-mediated neuroinflammation in the striatum remains unknown.…”
Section: Introductionmentioning
confidence: 99%